Falling for Figaro [videorecording (DVD)] - Lewin, Ben, 1946-; Lewin, Ben, 1946-; Macdonald, Danielle, 1991-; Skinner, Hugh, 1985-; Lumley, Joanna (RLJE Films, 2022)
A young woman decides to quit her job as a fund manager, leave her long-term boyfriend, and pursue her dream of becoming an opera singer in the Scottish Highlands.